2018
DOI: 10.1108/aaaj-07-2017-3028
|View full text |Cite
|
Sign up to set email alerts
|

Accountability practices in microfinance: cultural translation and the role of intermediaries

Abstract: Purpose The purpose of this paper is to explore how accountability practices are affected and potentially transformed when mediated by translation. Adopting a postcolonial lens, the authors consider the ways in which translation functions and how intermediaries act as cultural translators in the context of microfinance. Design/methodology/approach The authors take a qualitative approach to a case study of a microfinance organization based in South Africa. Fieldwork allowed for the collection of data by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
11
0
2
Order By: Relevance
“…Their attention to one tool is unique and uncovered four factors critical to the tool's success: its design; its appreciation of the local culture; the nature of its distribution by fieldworkers; and its responsiveness to the MFI clients' perspective. The paper indirectly problematizes notions of downward accountability by illustrating how certain accountability tools need to be tailored to the needs of "clients" if they are to be effective (see also Marini et al, 2018).…”
Section: Reflecting On the 2006 Special Issuementioning
confidence: 99%
“…Their attention to one tool is unique and uncovered four factors critical to the tool's success: its design; its appreciation of the local culture; the nature of its distribution by fieldworkers; and its responsiveness to the MFI clients' perspective. The paper indirectly problematizes notions of downward accountability by illustrating how certain accountability tools need to be tailored to the needs of "clients" if they are to be effective (see also Marini et al, 2018).…”
Section: Reflecting On the 2006 Special Issuementioning
confidence: 99%
“…The contributions to this AAAJ special issue also demonstrated that there is much still to be done for us as a community to begin to comprehend and address the impact of language and translation on our innovative and (hopefully) more inclusive knowledge creation endeavors. Thus, there is a considerable scope for the exploration of the power implications of language skills, and of the use of ELF, in diverse settings (Detzen and Loehlein, 2018;Evans, 2018b;Kamla and Komori, 2018;Locke et al, 2018;Marini et al, 2018). Several papers also draw attention to the opportunities relating to the agency, power (or lack of power), standing and motives of the translator and the interests in and politics of decision making in translation (see, especially, Ejiogu and Ejiogu, 2018;Evans, 2018b;Kamla and Komori, 2018;Nobes and Stadler, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Kamla and Komori (2018) challenge us to find new ways to interact with, and disseminate knowledge about, local communities without inadvertently reinforcing stereotypes and hegemonies. Research is also required to address the power imbalances arising from translation of western conceptssuch as accountabilityinto local cultures, and to develop new (hybrid) forms of accountability that better serve the needs of, and better preserve local cultures and practices (Marini et al, 2018). One way to achieve such better translation is by being more transparent in describing and reflecting on our methods and their inherent power implications and by emphasizing and exploring, rather than obscuring, differences (Kamla and Komori, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Konsep akuntabilitas sebenarnya jauh lebih luas, yaitu proses di mana organisasi berkewajiban menyediakan informasi tentang apa yang diyakini, dilakukan atau tidak dilakukan, dan melibatkan pemangku kepentingan secara aktif serta menanggapi pandangan dan kritik terhadapnya (Mutiganda, 2013). Penelitian Hyndman & McKillop (2018) dan Marini, Andrew, & Laan (2018) menemukan bahwa terdapat beberapa faktor yang menyebabkan seringkali terdapat bias pada penentuan sebuah oganisasi atau bisnis akuntabel atau tidak, antara lain kepercayaan, emosi, intuisi (kata hati), kontrak sosial, dan hubungan timbal balik yang bercampur.…”
unclassified